Hypothermia and cold injuries in children and young people. (11th August 2022) - Camara, Claire; Watson, Chloe
Abstract : Although hypothermia and cold injuries are rare in children and young people in the UK, the risk is persistent and requires urgent medical management when it does occur. This article outlines some considerations for professionals who may be caring for hypothermic patients or those at risk of becoming hypothermic.